2000
DOI: 10.1104/pp.123.4.1495
|View full text |Cite
|
Sign up to set email alerts
|

At-ACA8 Encodes a Plasma Membrane-Localized Calcium-ATPase of Arabidopsis with a Calmodulin-Binding Domain at the N Terminus

Abstract: A Ca 2ϩ -ATPase was purified from plasma membranes (PM) isolated from Arabidopsis cultured cells by calmodulin (CaM)-affinity chromatography. Three tryptic fragments from the protein were microsequenced and the corresponding cDNA was amplified by polymerase chain reaction using primers designed from the microsequences of the tryptic fragments. At-ACA8 (Arabidopsis-autoinhibited Ca 2ϩ -ATPase, isoform 8, accession no. AJ249352) encodes a 1,074 amino acid protein with 10 putative transmembrane domains, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
153
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(162 citation statements)
references
References 57 publications
6
153
0
3
Order By: Relevance
“…We therefore propose that PCA1 is required to restore the [Ca 2+ ] cyt for the generation of a stimulus- specific transient increase in [Ca 2+ ] cyt (3,47) PCA1 was localized in membranes of small vacuolar compartments, which is consistent with the localization of the Arabidopsis P IIB -type Ca 2+ -ATPase ACA4 (16). The additional subcellular localization sites of plant P IIB -type Ca 2+ -ATPases in the plasma membrane (17,36), the ER (37), and the central vacuole (38) point to functional diversities within the plasma membrane and the endomembrane system in relation to Ca 2+ homeostasis and Ca 2+ signaling. Besides Ca 2+ -ATPases, Ca 2+ /H + exchangers control Ca 2+ homeostasis under stress conditions as Arabidopsis T-DNA mutants of the CAX1 Ca 2+ /H + antiporter displayed an enhanced freezing tolerance that was correlated with an elevated expression of CBF/DREB1 genes and their corresponding targets (48).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We therefore propose that PCA1 is required to restore the [Ca 2+ ] cyt for the generation of a stimulus- specific transient increase in [Ca 2+ ] cyt (3,47) PCA1 was localized in membranes of small vacuolar compartments, which is consistent with the localization of the Arabidopsis P IIB -type Ca 2+ -ATPase ACA4 (16). The additional subcellular localization sites of plant P IIB -type Ca 2+ -ATPases in the plasma membrane (17,36), the ER (37), and the central vacuole (38) point to functional diversities within the plasma membrane and the endomembrane system in relation to Ca 2+ homeostasis and Ca 2+ signaling. Besides Ca 2+ -ATPases, Ca 2+ /H + exchangers control Ca 2+ homeostasis under stress conditions as Arabidopsis T-DNA mutants of the CAX1 Ca 2+ /H + antiporter displayed an enhanced freezing tolerance that was correlated with an elevated expression of CBF/DREB1 genes and their corresponding targets (48).…”
Section: Discussionsupporting
confidence: 64%
“…Exploring the intracellular localization of Ca 2+ -ATPases may provide insights into the subcellular compartments that are involved in the maintenance of low [Ca 2+ ] cyt . Previous studies indicated a diverse localization of plant P IIB -type Ca 2+ -ATPases in the plasma membrane (17,36), the endoplasmic reticulum (ER) (37), small vacuoles (16), and the central vacuole (38). To analyze the localization of PCA1, we fused the cDNA of the GFP to the 3′ end of the PCA1 coding region under the control of the cauliflower mosaic virus 35S promoter and transfected the construct into Physcomitrella protoplasts that were analyzed by confocal laser scanning microscopy 48 h after the transformation.…”
Section: Resultsmentioning
confidence: 99%
“…These Ca 2+ ATPases comprise 10 transmembrane-spanning domains, harbor a calmodulin-binding domain for autoinhibition of the ATPase active site, and can localize to different membrane compartments (Boursiac and Harper, 2007). ACA8, ACA9, and ACA10 group into a distinct subfamily and accumulate at the plasma membrane (Bonza et al, 2000;Hwang et al, 2000;Lee et al, 2007). Whereas ACA9 expression is restricted to pollen and thereby is critical for pollen tube development, ACA8 and ACA10 are expressed throughout the plant and have not yet been assigned any specific function besides inflorescence growth (Schiøtt et al, 2004).…”
Section: Aca8 Interacts With Fls2 and Other Rksmentioning
confidence: 99%
“…ACA8 has been shown to mediate Ca 2+ transport in yeast and is activated by the binding of calmodulin (CaM) to its N terminus (Bonza et al, 2000Mersmann et al, 2010). Based on the interaction of ACA8 with FLS2, we addressed whether ACA8 and ACA10 function in the flg22-triggered Ca 2+ burst.…”
Section: Flg22-triggered Early Responses Depend On Aca8 and Aca10 Funmentioning
confidence: 99%
“…Although the ACAs are most closely related to the animal plasma membrane Ca 2ϩ ATPases, they are distinct in (i) having isoforms located in the endoplasmic reticulum and tonoplast, in addition to the plasma membrane and (ii) having their calmodulin-regulated autoinhibitor located at the Nterminal instead of C-terminal end (21)(22)(23). Based on amino acid similarity and intron positions, ACAs can be divided into 4 subfamilies (20), with ACA8, ACA9, and ACA10 constituting subfamily 4 (Fig.…”
mentioning
confidence: 99%